The romantic myth of Jean-Gaspard Deburau - Nye, E (University of Nebraska Press, 2015)
Jean-Gaspard Deburau is renowned for being the greatest and most influential mime artist before Marcel Marceau (who himself was influenced by Deburau) in the twentieth century. Such was his standing in the 1830s and 1840s that a veritable myth was created around him, which has persisted ever since (for example, in the legendary French film Les Enfants du paradis). The contemporary discourse on Deburau was, to some extent, a constructed discourse intended to turn him into a symbol of certain Romantic ideals. In order to understand the myth of Deburau and his theatre, Le Théâtre des Funambules, I summarize the qualities which contemporaries so admired in his Pierrot role, and then consider some of them in the light of four Romantic topoï: nostalgia for the Commedia dell’arte, the image of the working-class artist, of the Bohemian artist, and of the sick artist.